Case study: company analysis Richiamo Coffee UiTM Arau / Alya Yusra Ismail … [et al.] - Ismail, Alya Yusra; Mohd Sampri, Nur Iffah; Noramat, Ummi Nur Zahirah; Zakariya, Nur Syafiqah (2022)
Coffee is one of the world's most famous beverages. For those who are coffee lovers, there are a few coffee shops that have many flavors for those who are interested. Now, there are many well-known brands in the market that produce coffee shops. Therefore, we are undertaking a case study on Richiamo Coffee, a firm in the food and beverage industry, and through it, we also want to learn more about the Business Model Canvas (BMC). In March 2021, Richiamo Coffee opened a new branch at UiTM Arau, Perlis and received a good response from the public such as students, staff, and others. Besides, Richiamo is also known for its delicious food and drinks, especially caffeinated drinks. All coffee shops in Malaysia have a mission and vision as well as Richiamo Coffee which has a good mission and vision to become famous in the eyes of the public and also to achieve goals by having a strong strategy. The business model canvas shows the customer segment of Richiamo Coffee is mainly university students who are coffee lovers and value quality coffee and an inviting atmosphere. Richiamo Coffee offers a wide variety of drinks, including traditional espresso-based drinks, cold brews, iced coffees and custom combinations because they provide the premium coffee beans that were imported from Italy. They sell coffee and tea including a variety of quality food and pastries and advertises their promotion through Facebook and Instagram by posting the feeds. Richiamo coffee has a problem especially in making coffee which is that each branch has a different coffee taste. Richiamo Coffee is also lacking in marketing to promote coffee and it will make it difficult for Richiamo to get new customers and to become one of the famous coffee shops in Perlis. To cope with these issue, Richiamo Coffee can make improvement by Standardize the Taste by create a SOP in making their products. Second, improve employees skills because different skills among employes will effect the taste of the drinks especially coffee. Offer a wide space also important because a large space can attract more customer to come especially students or career people for doing their business. Lastly, they need to improve marketing strategy by collaborate with famous influencer or else. After going through to the discussion, we came out to create our own company. We decided to set a coffee shop that offer decaffeinated drinks to our customer. We believe that decaffeinated options are becoming more popular among coffee drinkers, health-conscious consumers, and those people who prefer to consume less caffeine. We also give option for customer to select their cup sizes, including standard, and large cups. As a final alternative to traditional plastic straws, we decided to use rice straw to make it more environmental friendly.